Real-time science operations to support a lunar polar volatiles rover mission. Issue 10 (15th May 2015) - Heldmann, Jennifer L.; Colaprete, Anthony; Elphic, Richard C.; Mattes, Greg; Ennico, Kimberly; Fritzler, Erin; Marinova, Margarita M.; McMurray, Robert; Morse, Stephanie; Roush, Ted L.; Stoker, Carol R.
Highlights In situ resource utilization will be an enabling function for long duration human lunar exploration. Prior to lunar ISRU, natural resources must be identified and characterized. Precursor ISRU missions require real-time science operations demonstrated via terrestrial fieldwork.